Key Technique Study of Stability Control of Surrounding Rock in Deep Chamber with Large Cross-Section: A Case Study of the Zhangji Coal Mine in China - Yao, Weijing; Pang, Jianyong; Zhang, Jinsong; Liu, Guangcheng (Geotechnical and geological engineering, 2021)
This paper is a case study on the key technique of stability control of surrounding rock in the deep chamber with large cross-section in Zhangji Coal Mine of China. Many investigations and field experiments were performed to reveal the surrounding rock failure mechanisms of the chamber. It was found that the large cross-section, high in situ stresses, large rock zone and construction disturbance were the main causes of the chamber instabilities. For the original supporting scheme, the numerical simulation was adopted to analyze the surrounding rock stress and displacement during excavation and support. There are stress concentrations and large displacement at the junction of the chamber, shaft lining, and machine roadway. The maximum displacements are 74.7 mm in horizontal, 105.9 mm roof fall and 29.2 mm floor heave in vertical. Based on the simulation results, the supporting structure optimization design of the chamber has been completed. The primary supporting structure is composed of the bolt, steel mesh, shotcrete and anchor. The secondary supporting is concrete lining with double-layer reinforcement and an inverted arch. The shallow and deep lagging grouting technique was adopted for reinforcing rock. The three-dimensional steel grid inverted arch lining was developed independently. The indoor model test showed that the inverted arch lining can take advantages and characteristics of various materials through unique spatial network design, which improved the whole bearing capacity. A field experiment of convergence and reinforcement stress monitoring was conducted. The field measurement data showed that the maximum displacement of two sides and roof were 60 mm and 42 mm at 200 days, respectively. The reinforcement stresses of supporting structure were far less than the yield strength, which had a higher safety stock. This successful case study demonstrated that the optimized supporting structure is reasonable and the deformation of surrounding rock has been effectively controlled.